FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN PEKERJA BATU BATA DI DESA MEKAR BARU KECAMATAN BANAWA TENGAH - Rustam, Rustam (Katalogis, 2015)
This study aims to: (1) To determine the income of working people in the brick industry in Mekar Baru, Central Banawa District; and (2) To determine the impact of workers’ age, working time period and work experience toward the income the brick workers in the Mekar Baru village, District of Central Banawa. There are 52 people involved in this study as the sample. They are consists of 14 land owners, land processor 48 and 48 workers. The overall sample are chosen by proportionate stratified random sampling. The sampling is devided by dividing the population into homogeneous groups as called strata, and then the samples are taken randomly from each stratum. The approaches of data analysis in this research include income analysis and the Cobb-Douglass production function. The results show that: (1) The average earned income by the brick workers in the Mekar Baru village, Central Banawa District, Donggala regency is merely sufficient to meet the basic needs in their daily life; and (2) all the observed factors have simoultaneously impact on the income of brick workers bricks in the village of Mekar Baru. However, the working time period has partially and significant factor on the brick workers while working time period (X2) and the age of workers (X1) as well as working experience (X3) have not significant impact on the brick workers in the Mekar Baru village, Central Banawa district, Donggala regency .